Upaya Membangun Karakter Peserta Didik Melalui Literasi Digital Dalam Tantangan Pendidikan Abad 21 - Rika Yohana (Universitas Sebelas Maret, 2020)
Living conditions in the 21st century are full of challenges and competition. This has an impact, among others, on the level of great mental stress in addition to the availability of opportunities for those who have life competence, and have multiliteracy that strengthens the physical, mental, and intellectual capacities of students. Therefore digital literacy needs to be developed in today's world of education to build a better national character and be more prepared to face the 21st century learning era. The purpose of compiling this article is to find out how the method of building student character as elementary school level students through digital literacy (Digitalage Literacy) in education to face 21st century education. have an understanding of these digital literal dimensions and can develop materials and procedures for digital literacy education in school and outside of school, in order to face the era of 21st century education.